2022
DOI: 10.1007/s10875-022-01351-0
|View full text |Cite
|
Sign up to set email alerts
|

Three Adult Cases of STAT1 Gain-of-Function with Chronic Mucocutaneous Candidiasis Treated with JAK Inhibitors

Abstract: Purpose The aim of this study was to characterize clinical effects and biomarkers in three patients with chronic mucocutaneous candidiasis (CMC) caused by gain-of-function (GOF) mutations in the STAT1 gene during treatment with Janus kinase (JAK) inhibitors. Methods Mass cytometry (CyTOF) was used to characterize mononuclear leukocyte populations and Olink assay to quantify 265 plasma proteins. Flow-cytometric Assay for Specific Cell-mediated Immune-respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“… 40 Clinical trials have demonstrated a significant improvement in symptoms in patients with CMC with the use of JAK inhibitors for a short course, although side effects have been reported. 41 Therefore, JAK inhibitors or other gene-targeted drugs could be potential therapeutic options in the future treatment of CMC. 42 Single-cell sequencing of STAT-GOF patients with CMC revealed upregulation of tumor necrosis factor alpha-induced protein 3 (TNFAIP3).…”
Section: Discussionmentioning
confidence: 99%
“… 40 Clinical trials have demonstrated a significant improvement in symptoms in patients with CMC with the use of JAK inhibitors for a short course, although side effects have been reported. 41 Therefore, JAK inhibitors or other gene-targeted drugs could be potential therapeutic options in the future treatment of CMC. 42 Single-cell sequencing of STAT-GOF patients with CMC revealed upregulation of tumor necrosis factor alpha-induced protein 3 (TNFAIP3).…”
Section: Discussionmentioning
confidence: 99%
“… 23 In addition, there are also reports of successful treatment with baricitinib. 24 For cases that do not respond to conventional treatment, hematopoietic stem cell transplantation is another possible option. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, hematopoietic stem cell transplantation (HSCT) is the only curative treatment option, but the current literature indicates high rates of secondary graft failure and mortality [ 65 , 66 ]. The JAKinibs such as ruxolitinib or baricitinib, have been shown to effectively treat many of the aforementioned disease manifestations, and in particular CMC [ 67 , 68 , 69 , 70 , 71 ]. A recent study summarized the experience with JAKinibs in pediatric STAT1 GOF patients and showed a good response rate (82%; 18/22 subjects) after 1–8 weeks of therapy.…”
Section: Methodsmentioning
confidence: 99%